2014
DOI: 10.1080/02722011.2014.885541
|View full text |Cite
|
Sign up to set email alerts
|

Academic Migration at the Canada–US Border

Abstract: This article uses data provided by national faculty directories, individual and departmental websites, interviews, and autobiographical essays to engage the literature on academic migration at the Canada-US borderland. Our goal is to analyze the crossborder migration, spatial patterns, and motivational factors shaping the cross-border flows of academic migrants from one selected discipline. Following a foundational discussion of the related political, economic, and sociocultural push-pull factors influencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…() surveyed assistant professors employed in all 56 of Canada's sociology departments in 2012 and found that only five departments had fewer than 50 percent Canadian‐trained faculty (for similar trends, also see McLaughlin , ; Tremblay et al. ). Although the source of these discrepancies could be methodological in nature, these reports all seem to agree that larger research‐intensive universities tend to hire more foreign‐trained Ph.D.s.…”
Section: Current Struggles: Canadian Academe and International Fieldsmentioning
confidence: 97%
See 1 more Smart Citation
“…() surveyed assistant professors employed in all 56 of Canada's sociology departments in 2012 and found that only five departments had fewer than 50 percent Canadian‐trained faculty (for similar trends, also see McLaughlin , ; Tremblay et al. ). Although the source of these discrepancies could be methodological in nature, these reports all seem to agree that larger research‐intensive universities tend to hire more foreign‐trained Ph.D.s.…”
Section: Current Struggles: Canadian Academe and International Fieldsmentioning
confidence: 97%
“…The contemporary period from the late 1990s onward is marked by mass faculty retirement and replacement, notable changes to policies regarding faculty mandatory retirement (Worswick ), revisions to the Canadian First Policy guidelines (Tremblay, Hardwick, and O'Neill ), further entrenchment of internationalization strategies (Gingras ), and the emergence of global university rankings as powerful verticalizing technologies (Stack ). This move toward internationalization is described by Gingras () as the new dominant rhetoric that has come to equate “excellence” with “international,” a trend tending to favor the hiring of foreign scholars.…”
Section: Current Struggles: Canadian Academe and International Fieldsmentioning
confidence: 99%
“…Enthusiasts are those migrants who prefer to live and work in a given country. In the migration literature, they are denoted by many notions: Tremblay et al's (2014) academics motivated by "political and social factors", Siegerts's (2011) "Germanophiles", Vuin et al's (2016) "amenity migrants", or Benson and O'Reilly's (2009) "lifestyle migrants"to mention only a few examples. Slovak "enthusiasts" can be divided into those who are interested mainly in Slovakia or Central Europe (and have those regions as the geographical focus of their research) and those who came here out of curiosity to learn about a different region 13 .…”
Section: Local Enthusiastsmentioning
confidence: 99%
“…While the enthusiasts are present in core countries (see e.g. Siegert 2011;Tremblay's at al. 2014), it is unlikely that international last resort scholars find many positions there.…”
Section: When I Was Finishing My Studies In [Home Country] I Was Tryimentioning
confidence: 99%
“…The classic push-pull model originally stressed the migrant's economic cost-benefit calculation and later incorporated more sociological reasoning (Brettell & Hollifield, 2015). In higher education, the push-pull framework has mostly been applied to studies of international students (Mazzarol & Soutar, 2002), and international academic mobility and migration (Nunn & Price, 2005;Tremblay et al, 2014). The framework's basic assumption is that an individual's decision to migrate to a particular country in search of better opportunities is influenced by a combination of push-pull factors (Van Hear et al, 2017).…”
Section: Push-pull Factors For Understanding Academic Migrationmentioning
confidence: 99%